Comparison between roll-over test and placental localization for early prediction of preeclampsia - Walia, Moneet; D’souza, Aparajita Sophia; Gupta, Garima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preeclampsia is a common disorder of pregnancy and a major cause of maternal, foetal and neonatal mortality and morbidity. The roll-over test is based on the observation that significant supine hypertension is present for a period of 8 to 10 weeks prior to the onset of preeclampsia. The objective of the present study was to study and compare roll-over test with placental localization for early prediction of preeclampsia. Methods: In this prospective number bound study, a total of 200 unselected singleton pregnant females were included. All women were subjected to ultrasonography for placental localization at 24 weeks of gestation. They were subjected to roll-over test twice, first at 24 weeks and then at 28–30 weeks of gestation. Either the development of preeclampsia as per ACOG criteria or delivery was taken as end point in this study. Results: Of 200 women, 148 had a central placenta and 52 had a unilateral placenta. 37 women had preeclampsia, out of which 68 % had a unilateral placenta and 51 % had positive roll-over test. However when the roll-over test was performed at 24 weeks, it was negative in all study cases. So it had got no role as an early predictor of preeclampsia. Conclusions: This study concludes that ultrasonographic localization of the placenta seems to be a simple and easy to perform predictive test for incipient preeclampsia as compared to the roll-over test.